2014
DOI: 10.2478/s13536-014-0246-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and microstructural characterization of Si(100) Ce1−x GdxO2−δ thin films prepared by pulsed laser deposition technique

Abstract: Microstructural properties of Ce 1−x Gd x O 2−δ (x = 0 to 0.3) thin films prepared by pulsed laser deposition technique were studied. The thin films were deposited on Si(100) substrate at a substrate temperature of 973 K at the oxygen partial pressure of 0.2 Pa using KrF excimer laser with energy of 220 mJ. The prepared thin films were characterized by X-ray diffraction, Raman spectroscopy and atomic force microscopy. X-ray diffraction analysis confirmed the polycrystalline nature of the thin films. Crystallit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The dislocation density (δ) is defined as the length of dislocation lines per unit volume of the crystal and was determined using the following relation , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dislocation density (δ) is defined as the length of dislocation lines per unit volume of the crystal and was determined using the following relation , …”
Section: Resultsmentioning
confidence: 99%
“…where "θ" is the diffraction angle, "β" is full width at half maxima, and "λ" is the monochromatic X-ray wavelength. The dislocation density (δ) is defined as the length of dislocation lines per unit volume of the crystal and was determined using the following relation 23,24 Dislocation density is decreased with increasing substrate temperature, as the dislocation density indicates the dislocation network in the indium oxide thin films. The reduction in dislocation density reflects the emergence of good-quality thin films at higher deposition temperatures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…S1. The average mean grain size (MGS) of the NCs was calculated by the Debye- Scherer equation as follows 58,59 :where β is the broadening in the full-width at half maximum (FWHM), λ is the X-ray wavelength (1.5406 Å), and θ is the Bragg diffraction angle. The microstrain, ε , of the NCs is evaluated by
Figure 3XRD spectra of the cerium oxide nanocubes (CeO 2 NCs) as a function of urea concentrations.
…”
Section: Resultsmentioning
confidence: 99%
“…10 mol% Gd doped ceria powder was prepared by sol-gel method with commercially available cerium ammonium nitrate [Ce(NH 4 ) 2 (NO 3 ) 6 ] and gadolinium nitrate [Gd(NO 3 ) 3 ], having 99.99% purity were used as starting precursors. Synthesis process of 10 mol% Gd doped ceria powder by sol gel process was reported elsewhere [22]. The sol gel prepared Gd doped ceria powder has made into pellets with 20 mm diameter and 5 mm thickness at a pressure of 3 tons/cm 2 by using a hydraulic pelletizer.…”
Section: Methodsmentioning
confidence: 99%
“…Dislocation density ı = 1 (crystallite size) It is observed that the dislocation density and strain are found to decrease with increase of oxygen partial pressure. It is due to large number of collisions of ablated atoms that have a higher probability to agglomerate before reaching the substrate [22]. The variation of strain (ε) and dislocation density (ı) with oxygen partial pressures of the Gd doped ceria thin films are tabulated in Table 1.…”
Section: X-ray Diffractionmentioning
confidence: 99%